1980
DOI: 10.1071/ar9800589
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of protein from forage diets in the small intestine of the sheep

Abstract: The digestion of nitrogen other than ammonia (NAN) in the small intestine of sheep fed on forage diets has been estimated by developing a structural relationship y = a+bx, where y = NAN (g/d) leaving the ilium and x = NAN leaving the abomasum. In this relationship the intercept a represents endogenous NAN passing from the ileum and the slope b the indigestibility of abomasal NAN; hence ( 1-b ) gives true digestibility. The values obtained (mean &SE) were: a = 1.04�0.32 and b = 0.34 � 0.02 , which indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
13
2
Order By: Relevance
“…However, as the absorption of exogenous protein is not affected by parasitism then the increased flow of NAN at the ileum presumably represents endogenous amino acids, mostly epithelial cells and mucus protein. Mucus secretions are high in S amino acids, threonine and histidine (Clarke et al 1966;Lindsay et al 1980;Steel & Symons, 1982) and this could result in a loss of these essential amino acids through incomplete resorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the absorption of exogenous protein is not affected by parasitism then the increased flow of NAN at the ileum presumably represents endogenous amino acids, mostly epithelial cells and mucus protein. Mucus secretions are high in S amino acids, threonine and histidine (Clarke et al 1966;Lindsay et al 1980;Steel & Symons, 1982) and this could result in a loss of these essential amino acids through incomplete resorption.…”
Section: Discussionmentioning
confidence: 99%
“…This would require that the remainder of the extra ileal NAN (0.3 g NAN/d during weeks 5-7; 2.3 g NAN/d during weeks 11-13) arises from other endogenous secretions, perhaps either mucins or sloughed cells, or both. Lindsay et al (1980) suggested that theresorption of totalendogenous proteininnormal animalsmay be as highas 0.85-0.90. If, therefore, a similar value were applicable to the infected lambs this would require that during weeks 5-7 and 1 1-13 of dosing an extra 3-5 g NAN and 1 4 2 1 g NAN/d be secreted into the small intestine to account for the extra non-resorbed endogenous component at the ileum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, any elevation in digestive secretion losses will decrease the availability of these amino acids for protein synthesis and gain in other tissues. Most serious is the high concentration of threonine (280 mmoVmol), serine (130 mmoVmo1) and proline (130 mrnoUmol) in intestinal mucus (Neutra & Forstner, 1987), which is reported to be resistant to proteolytic degradation and poorly resorbed from the small intestine (Lindsay et al 1980). Another implication of the immunological resistance phase of infection relates to the availability of sulphur-amino acids for leukotriene production (Lewis & Austen, 1981).…”
Section: Consequences Of Infection O N T H E Availability Of I N D I mentioning
confidence: 99%
“…Additionally, mucus has been reported to be resistant to digestion and resorption from the small intestine (Lindsay et al, 1980). When mucus is formed, its component amino acids are effectively unavailable for reuse in synthesis of other proteins (Knox et al, 2006).…”
Section: Nutrient Metabolismmentioning
confidence: 99%